PENGARUH KUALITAS AUDIT TERHADAP HUBUNGAN EARNINGS MANAGEMENT DAN RETURN SAHAM - Indri Rahayu; Deni Darmawati (Media Riset Akuntansi, Auditing & Informasi, 2011)
The objective of the empirical study is to examine and to analyze the effect ofAudit Quality on the relation of Earnings Management and Stock Return. The other objective of this research is to compare two measurements of audit quality that is specialization industry auditor and brand name auditor. The sample of this empirical study is the manufacturing company that listed in Bursa Efek Indonesia (BEI) in 2009. The result of this empirical study are (1) the earnings management is positive directly have an impact to the stock return. (2) Audit Quality that was measure by specialization auditor and by brand name auditor showed that Audit Quality weaken off the positive impact of relation on earnings management to the stock return. In another word, Audit Quality is functioned to reduce market reaction failure caused by financial information which contained earnings management.Keywords: Earnings Management, Audit Quality, Industry SpecializationAuditor, Brand Name Auditor, Stock Return